Upotocznienie języka jako sposób budowania narracji w biografii sportowca (na materiale biografii Roberta Lewandowskiego) - IWONA PAŁUCKA-CZERNIAK (Stylistyka)
The analysis serves to present the communication strategy used in building a narrative in the athlete’s biography, which involves changing the official language to an unofficial one, saturating the message with colloquialism and commonness, and introducing elements of live speech into the written text. The phenomenon is presented with the example of the biography of the contemporary Polish footballer, Robert Lewandowski, written by Paweł Wilkowicz. The analysed implementation of the biography genre shows a cross-border approach to genological determinants. The text has muddled and blurred genre features. It concerns a living person and is created with his participation. It combines an objective, external narrative with a subjective, internal approach. The latter strategy allows for a purposeful, reflective definition of one’s own identity, its construction and creation. The difference, duality and contradiction between genres is consolidated in the text and language, and allows for reconstructing various strategies of talking about the book’s hero and his fate. Making the language of biography colloquial by saturating it with elements of live speech, lexis belonging to an unofficial variety of the language, colloquialism and expressiveness, and finally ensuring a smooth transition in the narrative from the language of the people interviewed to the language of the narrator, are related to the specificity of a communicative community, and to the idea of which the biography is being written. It also results from the use of an interview as a form of obtaining information by a journalist, which contributes to the introduction of colloquiality and the abandonment of the official nature of the message.